Predicted long-term antibody persistence for a tick-borne encephalitis vaccine: results from a modeling study beyond 10 years after a booster dose following different primary vaccination schedules - Costantini, Marco; Callegaro, Andrea; Beran, Jiří; Berlaimont, Valérie; Galgani, Ilaria (Human vaccines & immunotherapeutics, 2020)
In tick-borne encephalitis (TBE)-endemic regions, long-term vaccination programs are efficient in preventing the disease. A booster dose of a polygeline-free inactivated TBE vaccine (Encepur Adults, GSK), administered approximately 3 years post-primary vaccination according to 1 of 3 licensed vaccination schedules in adults and adolescents, resulted in antibody persistence for 10 years post-boosting. We used different power-law models (PLMs) to predict long-term persistence of anti-TBE virus neutralization test (NT) antibody titers over a period of 20 years post-booster dose, based on individual antibody NT titers measured for 10 years post-booster vaccination. The PLMs were fitted on pooled data for all vaccine schedules. A mean NT titer of 261 (95% prediction interval: 22-3096), considerably above the accepted threshold of protection (NT titers ≥10), was predicted 20 years post-booster vaccination with TBE vaccine. Our modeled data suggest that the intervals of booster doses could be increased without compromising protection against TBE.
Keywords: protilátky virové; Immunization, Secondary; Adolescent; Adult; Encephalitis Viruses, Tick-Borne; dospělí; Tick-borne encephalitis; mladiství; Encephalitis, Tick-Borne; vakcinace; Viral Vaccines; sekundární imunizace; lidé; Humans; statistical model; klíšťová encefalitida; polygeline-free inactivated TBE vaccine; Vaccination; Antibodies, Viral; viry klíšťové encefalitidy; power-law model; virové vakcíny; antibody persistence